Web-based Collaborative Learning: Students’ Feedback on the Communication and Interaction Processes - Leow, Fui Theng; Neo, Mai (IEEE, 2013)
The emergences of information technologies and World Wide Web have broadened the horizon of innovative teaching and learning, and have pushed the bar on web-based collaborative learning. This includes expanding the social interaction and engagement between the students with more online communication and collaborative tools. Hence it established the importance of analyzing the processes in social interaction and online communication, and further developed the framework to evaluate the design of this learning environment which can sustain and support web-based collaborative learning. Many learning approaches today have embedded collaborative learning activities and therefore there is a need to investigate the effectiveness of such collaborations with respect to student communication and interactions. This study presents students’ feedback on their interaction and communication process when collaborating on a multimedia project. The Communicative Model of Collaborative Learning (CMCL) was used to analyze their feedback, obtained from open-ended questions and student interviews. The results showed that the CMCL was a useful tool for assessing the linguistic interactions between students in this strategy of web-mediated learning. The results showed positive encouragement for using the CMCL to further improve student communication and interaction analysis in web-based collaborative learning environments.